2009
DOI: 10.1063/1.3125255
|View full text |Cite
|
Sign up to set email alerts
|

Study of a nitrogen-doped ZnO film with synchrotron radiation

Abstract: X-ray absorption near-edge spectroscopy (XANES) and photoelectron spectroscopy (PES) with synchrotron radiation have been applied to investigate the structure and chemical states of nitrogen atoms in ZnO:N films with different annealing temperatures. The high-resolution XANES and PES spectra of N 1s reveal the chemical states of N dopants and give a direct observation of nitrogen location in the ZnO films. The results indicate that only the nitrogen atoms incorporated substitutionally at O sites act as accepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
12
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 29 publications
5
12
0
Order By: Relevance
“…These peaks, close to the vibrational energy of N 2 in air, are assigned to lattice-bound N 2 in ZnO. P 3 peak is similar to that of the characteristic absorption peak of N 2 O and has been attributed to the N 1s to 2pσ * transition in N-O species [18]. Accordingly, P 3 is ascribed to N at Zn sites.…”
Section: Methodsmentioning
confidence: 68%
“…These peaks, close to the vibrational energy of N 2 in air, are assigned to lattice-bound N 2 in ZnO. P 3 peak is similar to that of the characteristic absorption peak of N 2 O and has been attributed to the N 1s to 2pσ * transition in N-O species [18]. Accordingly, P 3 is ascribed to N at Zn sites.…”
Section: Methodsmentioning
confidence: 68%
“…It is obvious that each of the spectra has three N 1s peaks, located near the binding energy of 395.5, 399.2, and 404.8 eV, correspond to N-Zn, 9,10 C-N bonds, 11 and N-N pair at O site (N 2(O) ), 12 respectively. The content of N O is calculated to be 0.67 and 0.29 at.…”
mentioning
confidence: 99%
“…[18][19][20] However, studies have since shown that N-doping compensates p-type behaviour by forming shallow donors rather than acceptors, consequently p-type ZnO is unlikely to form. [21][22][23][24][25] Point defects situated deep in the ZnO bandgap (E g ) give rise to photoluminescence (PL) referred to as deep-level emission (DLE) observed under excitation >E g . This DLE emission has been employed in visible light-emitting diodes 26,27 and photodetectors.…”
Section: Introductionmentioning
confidence: 99%